The Politics of the Société Saint-Jean-Baptiste de Montréal - Agen, Marie-Catherine (American Review of Canadian Studies, 1999)
Keywords: Francophones; Nationalisme; Société Saint-Jean-Baptiste

A Social Refuse! L'assistance et la perception des vagabonds à Montréal à la fin du XIXe et au début du XXe siècles - Aranguiz, Marcela (Université du Québec à Montréal, 1999)
Keywords: Itinérance

L'Assistance maternelle de Montréal (1912-1961): un exemple de marginalisation des bénévoles dans le domaine des soins aux accouchées - Baillargeon, Denyse (Dynamis, 1999)
Keywords: Assistance maternelle; Femmes

Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Keywords: Crise; Famille; Femmes

Praticiennes et patientes. Les femmes et la santé dans l'historiographie québécoise - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1999)
Keywords: Femmes; Médecine

La pensée ouvrière et sociale de Joseph-Papin Archambault, s.j. (1880-1966) - Bélanger, Damien-Claude (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1999)
Keywords: Confédération des travailleurs catholiques du Canada (C.T.C.C.); Idéologies; École Sociale Populaire

Le mouvement ouvrier juif au Canada (1904-1920) - Belkin, Simon (Septentrion, 1999)
Keywords: Congrès juif canadien; Juifs; Poalei Zion (Mouvement sioniste ouvrier)

Parcours d'un marqueur sociolinguistique: les pronoms non-clitiques du pluriel en français parlé de Montréal - Blondeau, Hélène (Université de Montréal, 1999)
Keywords: Langue

L'architecture de la géographie scolaire québécoise: 1804-1960 - Brosseau, Marc (Cahiers de géographie du Québec, 1999)
Keywords: Géographie physique

The 'Links' on HIV & AIDS: An Examination of the Construction of HIV & AIDS in The Link - Castellana, Mariella (Université Concordia, 1999)
Keywords: Étudiants

Montréal à l'époque du Refus Global. Le climat social et religieux - Chaussé, Gilles (Montréal en tête, 1999)
Keywords: Communautés religieuses; Églises

L'Institut de réadaptation de Montréal: 50 ans d'histoire - Choquette, Danielle (L'Institut, 1999)

Les fondements du plan directeur. Volume 1 - Cimetière Notre-Dame-Des-Neiges (1999)
Keywords: Cimetières; Notre-Dame-des-Neiges (cimetière)

L'unilinguisme français et le projet souverainiste du Parti québécois vus par la communauté juive du Québec (1974-1981) - Cloutier, Caroline (Bulletin d'histoire politique, 1999)
Keywords: Juifs; Langue; Nationalisme; Partis politiques

Les cours d'instruction civique de la Fédération Nationale Saint-Jean-Baptiste. Une voie d'accès à la citoyenneté politique pour les femmes du Québec - Cohen, Yolande; Maillé, Chantal (Recherches féministes, 1999)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

La communauté médicale montréalaise de 1850 à 1890: variations sur le thème d'élite - Collin, Johanne; Monnais-Rousselot, Laurence (Histoire sociale / Social History, 1999)
Keywords: Médecine

Understanding the Patterns of Language Use of Chinese Children in a Montreal Community School - Curdt-Christiansen, Xiao Lan (Université McGill, 1999)
Keywords: Chinois; Langue; Étudiants

Le patronage Saint-Vincent-de-Paul de Montréal: (1892-1913) - Divay, Stéphane (Université d'Angers, 1999)
Keywords: Saint-Vincent-de-Paul (Société)

La déficience intellectuelle au Québec entre 1867 et 1921: de l'idiotie à l'arriération mentale - Dufort, Jean-Yves (Université de Sherbrooke, 1999)
Keywords: Hôpitaux psychiatriques; Médecine; Psychologie

Art Therapy: Three Models of Community-Based Mental Health Facilities - Durst, Adrienne (Université Concordia, 1999)

La colocation comme situation de communication interculturelle, le discours de cinq jeunes français vivant avec des québécois - Ferrand, Nathalie (Université du Québec à Montréal, 1999)
Keywords: Français; Locataires; Logement

Michel Chartrand: les voies d'un homme de parole - Foisy, Fernand (Lanctôt, 1999)
Keywords: Confédération des travailleurs catholiques du Canada (C.T.C.C.); Fédération des travailleurs et travailleuses du Québec (FTQ); Grèves; Travail

"Des Québécois importés et leurs niches": l'immigration et l'expression de l'ethnicité dans les pratiques économiques des Portugais indépendants du Québec - Fonséca, Félix (Université Laval, 1999)
Keywords: Portugais

Réflexions sur les pratiques communicationnelles des institutions de la société d'accueil dans l'insertion des immigrantes et des immigrants au Québec: 1986-1996 - Fournel, Claude-Jean (Université du Québec à Montréal, 1999)

Les écoles de Dorval / The Schools of Dorval - Fulleringer, Pat (Héritage Dorval, 1999)

Exile, Transnational Connections, and the Construction of Identity: Tibetan Immigrants in Montreal - Gardner, Jane (Université Concordia, 1999)
Keywords: Tibétains

Strategic Responses to the Geographical Problems of Women's Fear: A Case Study of Concordia University's Student Safety Patrol - Gerald, Clearlight (Université Concordia, 1999)
Keywords: Femmes; Université Concordia

Les quartiers multiethniques montréalais: une lecture urbaine - Germain, Annick (Recherches sociographiques, 1999)
Keywords: Quartiers

Solidarité et détermination : histoire de la Fraternité des policiers et policières de la Communauté urbaine de Montréal - Goulet, Henri; Rouillard, Jacques (Boréal, 1999)
Keywords: Police

Les monstres, les fous et les autres: la folie criminelle au Québec - Grenier, Guy (Trait d'Union, 1999)
Keywords: Criminalité; Hôpitaux; Hôpitaux psychiatriques

English Caribbean Immigrant Entrepreneurs in Montreal - Hall, Margaret-Ann (Université Concordia, 1999)
Keywords: Anglophones; Caribéens

Association des locataires des Habitations Jeanne-Mance 1974-1999 - Hamel, Pierre; Marcotte, Berthe (Association des locataires des Habitations Jeanne-Mance, 1999)
Keywords: Locataires; Logement

Writing Bodies: Modern Dance, Gender, and Jewish Identity in New York and Montreal, 1930 to 1960 - Hardt, Yvonne (Université Concordia, 1999)
Keywords: Danse; Juifs

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

De la clandestinité à l'affirmation: pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)

A Neighborhood that Empowers Women: In Search of Housing Sustainability - Insaf, Zeenat S. (Université McGill, 1999)
Keywords: Femmes; Logement

Les immigrants préférés: Les Belges - Jaumain, Serge (Presses de l'Université d'Ottawa, 1999)
Keywords: Belges

L'immigration belge au Canada: une histoire en devenir - Jaumain, Serge; Sanfilippo, Matteo (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges

L'expérience vécue par des jeunes maghrébins dans des centres de réadaptation à Montréal - Jouiet, Rabina (Université de Montréal, 1999)
Keywords: Maghrébins

Portrait multidimensionnel de la pauvreté sur l'île de Montréal: une étude de la précarité et de la subsistance à partir des données du recensement de la population (1986 et 1996) - Julien, Frédéric (Université de Montréal, 1999)
Keywords: Pauvreté

Les statuts sociométriques et les profils d'acculturation d'élèves d'origine immigrante à Montréal - Kanouté, Fasal (Université de Montréal, 1999)
Keywords: Étudiants

Femmes et organisations environnementales, l'activisme au féminin: étude de cas - Laloux, Aurélie (Université du Québec à Montréal, 1999)
Keywords: Femmes; Groupes populaires

Histoire sociale des savoirs-faire infirmiers au Québec de 1870 à 1970 - Lamontagne, Esther (Université du Québec à Montréal, 1999)
Keywords: Infirmières

Les congrégations religieuses: de la France au Québec, 1880-1914. Tome 2: Au plus fort de la tourmente, 1901-1904 - Laperrière, Guy (Presses de l'Université Laval, 1999)
Keywords: Communautés religieuses

Oeuvres d'art de l'ancienne église de Saint-Jacques - Laroche, Ginette (Les chemins de la mémoire. Biens mobiliers du Québec, 1999)
Keywords: Arts sacrés; Saint-Jacques (église); Université du Québec à Montréal

Oeuvres d'art de l'église de St. Stephen - Laroche, Ginette (Les chemins de la mémoire. Biens mobiliers du Québec, 1999)
Keywords: Arts sacrés; Westmount; Églises

L'identité transnationale et l'installation des Chinois du Vietnâm à Montréal - LaRochelle, Jean (Université de Montréal, 1999)
Keywords: Chinois

L'Université McGill et la société québécoise francophone, 1951-1969 - Leduc, Bernard (Université de Montréal, 1999)
Keywords: Université McGill

Expulsion des immigrants indésirables à Montréal: 1911-1914 - Legeay, Guilaine (Université d'Angers, 1999)

La structure spatiale des déplacements pendulaires des femmes et des hommes dans la région de Montréal - Lemelin, André; Gatignol, Agnès (Cahiers de géographie du Québec, 1999)

La carrière polyvalente de Gustave Francq, figure marquante du syndicalisme international au Québec (1871-1952) - Leroux, Éric (Université de Montréal, 1999)
Keywords: Syndicats internationaux

Scènes de la vie en rouge. L’époque de Jeanne Corbin (1906-1944) - Lévesque, Andrée (Remue-ménage, 1999)
Keywords: Communistes

La muette éloquence des choses: collections et expositions missionnaires de la Compagnie de Jésus au Québec, de 1843 à 1946 - Lord, France (Université de Montréal, 1999)
Keywords: Communautés religieuses; Jésuites

L'attitude d'étudiants universitaires anglophones face à diverses variétés de français - Magnon, Céline (Université du Québec à Montréal, 1999)
Keywords: Anglophones; Français; Étudiants

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

L'efficacité de la procédure de règlement des griefs à la Ville de Montréal - Marleau, Patrick (Université de Montréal, 1999)

La presse catholique au Québec: 1910-1940 - Marquis, Dominique (Université du Québec à Montréal, 1999)
Keywords: Action catholique

The Mother House of the Grey Nuns: A Building History of the General Hospital - Martin, Tania (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l'étude de l'architecture au Canada, 1999)
Keywords: Communautés religieuses; Hôpital Général; Hôpitaux; Soeurs Grises

The History of the Tiffany Windows at the Erskine and American Church, Montreal - Mathieu, Christine Johanne (Université Concordia, 1999)
Keywords: American Presbyterian Church; Erskine (église); Vitraux; Églises

La gentrification à Montréal 1971-1991 - Métaireau, Béatrice (Études canadiennes / Canadian Studies, 1999)
Keywords: Logement; Quartiers

Changing Forms of Parish Renewal: Toward a Restructuring of the Parochial Model, 1950-1999 - Million, Margaret Mary (Université Concordia, 1999)

Des Italo-Belges au Canada: résultats d'une première enquête - Morelli, Anne (Les immigrants préférés: Les Belges, 1999)
Keywords: Belges; Italiens

Rethinking Juvenile Prostitution: Insights from Youths on the Street - Morris, Jason (Université McGill, 1999)
Keywords: Enfants; Prostitution

Entente cordiale? La section montréalaise du Fonds patriotique canadien, 1914-1923: le bénévolat de guerre à Montréal - Morton, Desmond (Revue d'histoire de l'Amérique française, 1999)
Keywords: Bénévolat; Guerre

Les relations interculturelles entre les immigrants d'origine sénégalaise et la population d'accueil québécoise: jalons d'une analyse des systèmes de représentation et des stratégies d'intégration - Ndoye, Amadou (Université Laval, 1999)
Keywords: Sénégalais

La transmission d'une mémoire sociale à travers quatre générations: le cas des Juifs ashkénazes à Montréal - Olazabal, J.-Ignace (Université de Montréal, 1999)
Keywords: Juifs

Being Ill with the Disease of Schizophrenia - Paulse, Mark (Université Concordia, 1999)

Histoire de la spécialisation médicale au Québec: le cas de la naissance de l'hématologie à l'hôpital Notre-Dame de Montréal, 1920-1960 - Piché, Sébastien (Université du Québec à Montréal, 1999)
Keywords: Hôpital Notre-Dame; Hôpitaux; Médecine

Le processus de l'escalade de l'antagonisme lors de l'échec du projet de déménagement de l'Hôtel-Dieu de Montréal - Piette, Isabelle (École des hautes études commerciales de Montréal, 1999)
Keywords: Hôpitaux; Hôtel-Dieu

Education and Integration of Immigrant Minorities: A Case Study of the Haitian Community in Quebec - Pompilus, Léopold (Université Concordia, 1999)
Keywords: Haïtiens

Becoming Native in a Foreign Land: Visual Culture, Sport, and Spectacle in the Construction of National Identity in Montreal, 1840-1885 - Poulter, Gillian (York University, 1999)
Keywords: Autochtones; Britanniques; Français

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

Analyse longitudinale du discours sur la décentralisation à la Commission des écoles catholiques de Montréal - Pundzius, Richard (École des hautes études commerciales de Montréal, 1999)
Keywords: Commission des écoles catholiques de Montréal

Motivation in Hip-Hop Graffiti Culture: The Site of Tension between Individual Desire, Peer Influence and Community Space - Rahn, Janice (Université Concordia, 1999)

Oeuvres d'art de la chapelle de l'Invention-de-la-Sainte-Croix - Raudsepp, Karl J. (Les chemins de la mémoire. Biens mobiliers du Québec, 1999)
Keywords: Arts sacrés; Églises

La famille juive à Montréal au tournant du XXe siècle - Soucy, Isabelle (Université du Québec à Montréal, 1999)
Keywords: Famille; Juifs

Langues, langage et nouvelles technologies de l'information: le cas d'ingénieurs francophones dans l'industrie de l'aérospatiale à Montréal - Teixeira, Cari A. (Université de Montréal, 1999)
Keywords: Francophones; Ingénieurs

Étude sur l'évolution d'enfants âgés de 6 à 12 ans et de leur famille suivis par les services externes des centres de réadaptation pour jeunes en difficulté d'adaptation des Centres jeunesse de Montréal - Touchette, Luc (Université de Sherbrooke, 1999)
Keywords: Enfants

Évaluation de sessions de formation en gestion du stress à l'Institut de cardiologie de Montréal - Tremblay, André (Université de Montréal, 1999)

La robe montréalaise bourgeoise, 1870-1883: clichés, tendances et contextes de consommation - Vallières, Nicole (Université Laval, 1999)
Keywords: Bourgeoisie; Vêtements

Les étudiants et les luttes dans les premiers temps de Duplessis - Vennat, Pierre (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1999)
Keywords: Mouvement étudiant; Université de Montréal; Étudiants

Coping with the HIV and AIDS Epidemic in HIV Seronegative Gay Males in Montreal - Watson, Scott C. A. (Université McGill, 1999)
Keywords: Épidémies

The Jackie Robinson Myth: Social Mobility and Race in Montreal, 1920-1960 - Williams, Dorothy W. (Université Concordia, 1999)
Keywords: Enseignants; Lord, Gwen; Lord, Richard; Noirs; Robinson, Jackie